Tackling nutrition in Odisha: Looking back, looking forward - Avula, Rasmi; Nguyen, Phuong Hong; Mishra, Nihar; Mitra, Devjit; Kohli, Neha; Menon, Purnima (International Food Policy Research Institute, 2020)
This report explores the state of nutrition in Odisha, assesses how nutrition outcomes changed in the state, and more importantly, and examines the road that lies ahead of Odisha on the journey to support better nutrition for the state. Nutrition progress in Odisha: Odisha has made more rapid progress in reducing child undernutrition than many other richer states. Particularly between 2006 and 2016, nutrition and health outcomes improved significantly in the state. The prevalence of stunting declined from 45 percent to 34.1 percent, although there was a marginal increase in wasting from 19.6 to 20.4 percent and in severe wasting from 5.2 to 6.4 percent. In 2018, a further decline was noted in the prevalence of stunting (28.9 percent) and wasting (12.9 percent). Although anemia among women of reproductive age declined by 10 percentage points between 2006 and 2016, it is still high, with over half the women in the state suffering from anemia. Exclusive breastfeeding for children under 6 months of age is an area of progress, improving from 50.8 percent in 2006 to 65.6 percent in 2016; the prevalence of low birth weight, however, remained nearly unchanged during this period (Kohli et al. 2017). Emerging nutritional challenges, such as noncommunicable diseases, are likely to create new challenges in coming years.